Implementasi Error Detection System Pada Komunikasi Serial Arduino Menggunakan Metode Cyclic Redundancy Check (CRC) - Reynald Novaldi; Sabriansyah Rizqika Akbar; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The high development of the IoT system current is directly proportional to the high development of the communication system. This does not cover the possibility of the exchange of data on the communications system 100%. It is influenced by factors of weather, noise, voltage on the System unstable and crosstalk. But the problems on the exchange of this data can be reduced or avoided by the method of error detection and error correction. There are various methods of error detection such as reed solomon code, hamming code, and cyclic redundancy check. Arduino uno is a mikrokontroller development in the field of Iot is fast, easy development making the Arduino Uno became widely used in the embedded systems and wireless sensor network. This research method using error detection that is cyclic redundancy check or CRC, CRC has high efficiency and accuracy in detecting an error in communication or exchange of data. CRC polynomial systems using linear feedback shift and division registers where the method is very efficient to implement in hardware or software. this research of CRC method implemented on two mikrokontroller the arduino interconnected via a serial communications i.e. I2C, SPI, and UART, and one of the arduino as a sender and the other one as the recipient of the data. From testing the functionality of the system error detection is obtained that the system can detect an error in the data correctly with percentage 100% time on testing and obtained results that systems with communication UART takes a faster than a system with SPI or I2C.